Influence of Antemortem and Slaughtering Practices on the pH of Pork and Chicken Meats. - Manalo, Monica R.; Gabriel, Alonzo A.
This study aimed to document and determine the effects of antemortem and slaughtering practices on the post-mortem pH of pork and chicken meats. Assessment of selected hog slaughterhouses (SHs) and poultry dressing plants (PDPs) located in Valenzuela City, Philippines was conducted to gather basic information regarding the practices of each plant. The post-mortem pH at 45 min and 24 h for pork (n = 39) and post-mortem pH at 20 min and 24 h for chicken (n = 24) meats produced on the visited plants were determined. Measured pH values were used as the basis for classifying meat quality as pale, soft, and exudative (PSE); dark, firm, and dry (DFD); and acceptable meat. Early post-mortem temperature was also determined in both types of meat. Ocular plant inspection revealed that the average age of pigs and chickens slaughtered were 4 mo and 40?45 d old, respectively. Animals were transported from farm to slaughterhouse in a forward open cab vehicle with a partition at a distance that ranged from 45?60 km for pigs and 65?172 km for chicken with a travel time of 1?3 h. The resting period of pigs prior to slaughter was 1.5?8 h and 2?4 h for chicken. Generally, a higher percentage of suspected DFD (38.46% vs. 30.30%) and PSE (17.95% vs. 6.06%) in pork meat was observed at early post-mortem pH in comparison to ultimate pH. The majority of the PSE-like meat came from pigs slaughtered using electric stunner while DFD incidence occurred from pigs with a short resting period prior to slaughter (1.5?2 h). For chicken meat, 29% of the samples were suspected PSE based on ultimate pH while the remaining 71% were meat with suspected acceptable quality. PSE-like meat was recorded from chicken transported from farm to abattoir with a longer travel period (3 h).
Keywords: Science -- Periodicals; Chicken; DFD; Pork; PSE; pH